Forschendes Lernen in der fach- und fachrichtungsbezogenen, universitären Lehrkräftebildung - Peuker, Birgit; Busker, Maike; Rautenstrauch, Hanne; Winkel, Jens (Wissenschaftliche Buchgesellschaft (wbg), 2023)
Research-based learning has experienced a renaissance in university teacher education, so that a variety of ideas are being developed for a stronger research orientation. In their contributions, the authors answer four questions about the implementation of research-based learning in their subject/discipline and provide information about the characteristics, challenges and opportunities of research-based learning. In their contributions, each subject/subject also presents a best practice example from teacher education for lower or upper secondary education (including vocational education). This volume is thus characterized by its focus on the subject- or discipline-related perspective on research-based learning, so that readers receive a multifaceted overview of research-based learning in the context of teacher education in different subjects and disciplines.